Adsorption of heavy metal onto biomass-derived activated carbon: review. Issue 7 (31st January 2023) - Wang, Baoying; Lan, Jingming; Bo, Chunmiao; Gong, Bolin; Ou, Junjie
Abstract : Physical and chemical properties of carbon are discussed. The keys factors for heavy metal removal are reviewed. Biomass is a suitable material for preparing activated carbon to remove heavy metals. Abstract : Due to the rapid development of the social economy and the massive increase in population, human beings continue to undertake processing, and commercial manufacturing activities of heavy metals, which has caused serious damage to the environment and human health. Heavy metals lead to serious environmental problems such as soil contamination and water pollution. Human health and the living environment are closely affected by the handling of heavy metals. Researchers must find several simple, economical and practical methods to adsorb heavy metals. Adsorption technology has been recognized as an efficient and economic strategy, exhibiting the advantages of recovering and reusing adsorbents. Biomass-derived activated carbon adsorbents offer large adjustable specific surface area, hierarchically porous structure, strong adsorption capacity, and excellent high economic applicability. This paper focuses on reviewing the preparation methods of biomass-derived activated carbon in the past five years. The application of representative biomass-derived activated carbon in the adsorption of heavy metals preferentially was described to optimize the critical parameters of the activation type of samples and process conditions. The key factors of the adsorbent, the physicochemical properties of the heavy metals, and the adsorption conditions affecting the adsorption of heavy metals are highlighted. In addition, the challenges faced by biomass-derived activated carbon are also discussed.